2019
DOI: 10.5603/njo.2019.0018
|View full text |Cite
|
Sign up to set email alerts
|

Management of melanoma metastases in the brain

Abstract: The basic principle for the diagnosis of melanoma metastases in the brain should be the management of multidisciplinary teams including at least a neurosurgeon, radiotherapist and clinical oncologist experienced in the treatment of melanoma and melanoma metastases in the CNS. Detection of brain lesions is associated with poor prognosis; metastases in the brain are the cause of death in 20-50% patients, and symptomatic tumours are a direct cause of death in about 90% patients. Treatment of melanoma with CNS met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
18

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 47 publications
0
11
0
18
Order By: Relevance
“…Although these results were favorable in terms of disease control and safety large prospective studies are required to confirm the efficacy of nivolumabradiation therapy combination [72]. Based on available data and our own analysis we have also concluded that combination therapy of nivolumab and SRS for patients with intracranial melanoma lesions can be considered as a safe method of treatment [73][74][75]. This combination seems especially effective due to multiple mechanisms of synergy between radiotherapy and immunotherapy including tumor-associated antigen release, MHC I expression elevation, cytokine and chemokine release, CD8+ T-cells APC cells infiltration or MDSC cells reduction within the tumor [76].…”
Section: Safety Of Nivolumab In Challenging Subgroups Of Patientsmentioning
confidence: 59%
“…Although these results were favorable in terms of disease control and safety large prospective studies are required to confirm the efficacy of nivolumabradiation therapy combination [72]. Based on available data and our own analysis we have also concluded that combination therapy of nivolumab and SRS for patients with intracranial melanoma lesions can be considered as a safe method of treatment [73][74][75]. This combination seems especially effective due to multiple mechanisms of synergy between radiotherapy and immunotherapy including tumor-associated antigen release, MHC I expression elevation, cytokine and chemokine release, CD8+ T-cells APC cells infiltration or MDSC cells reduction within the tumor [76].…”
Section: Safety Of Nivolumab In Challenging Subgroups Of Patientsmentioning
confidence: 59%
“…It seems that these chronic infections could suppress T cell function and theoretically could decrease the effectiveness (particularly in the case of severe HIV/AIDS with a low number of CD4 + T cells) [34]. The principles of procedures for patients with a diagnosis of melanoma with metastases to the CNS have been described in the paper "Management of brain metastases in melanoma" (Piotr Rutkowski, Dorota Kiprian, Monika Dudzisz-Śledź, Tomasz Świtaj, Radosław Michalik, Mateusz Spałek, Katarzyna Kozak, Tomasz Mandat) [35], similarly to the principles of action in the case of combining immunotherapy with radiotherapy "The role of radiotherapy in melanoma" (Mateusz Spałek, Anna M. Czarnecka), which was also presented in "Oncology in Clinical Practice" [36].…”
Section: Discussionmentioning
confidence: 99%
“…Almost a half of them will suffer from multiple lesions [8][9][10]. Large but old autopsy studies on died cancer patients, originating from period when autopsies have been performed routinely, showed a higher incidence that ranged between 9% and 26% [11,12]. However, since the incidence of BM increases with better control of systemic disease and prolonged time from initial cancer diagnosis, the real prevalence of cerebral metastases might be significantly higher.…”
Section: Introductionmentioning
confidence: 99%